2023
DOI: 10.1021/acs.energyfuels.3c00136
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Computational Fluid Dynamics Investigation of Mechanisms of Enhanced Oil Recovery via Nanoparticle-Surfactant Solutions

Abstract: The enhancement in surfactant performance at downhole conditions in the presence of nanomaterials has fascinated researchers’ interest regarding the applications of nanoparticle-surfactant (NPS) fluids as novel enhanced oil recovery (EOR) techniques. However, the governing EOR mechanisms of hydrocarbon recovery using NPS solutions are not yet explicit. Pore-scale visualization experiments clarify the dominant EOR mechanisms of fluid displacement and trapped/residual oil mobilization using NPS solutions. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…It can be used to investigate wettability control, ITF, emulsification, and flow path for oil displacement via nanofluid. According to previous studies, ,, during the micromodel test, nanofluid injection can mobilize residual oil not only from high-permeability zones but also from a small fraction of low-permeability zones. The results suggested that the “nanoparticle-surfactant” system offers greater improvement in the macroscopic and microscopic sweep efficiency of the aqueous fluid from the heterogeneous porous medium.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…It can be used to investigate wettability control, ITF, emulsification, and flow path for oil displacement via nanofluid. According to previous studies, ,, during the micromodel test, nanofluid injection can mobilize residual oil not only from high-permeability zones but also from a small fraction of low-permeability zones. The results suggested that the “nanoparticle-surfactant” system offers greater improvement in the macroscopic and microscopic sweep efficiency of the aqueous fluid from the heterogeneous porous medium.…”
Section: Introductionmentioning
confidence: 90%
“…Current studies indicated that the addition of conventional surfactants, such as SDS, - cetyltrimethylammonium bromide (CTAB), and Tween surfactant, into SiO 2 nanofluid results in a higher oil recovery compared to surfactant solutions or pure nanofluid alone. Yekeen et al conducted a micromodel test to investigate the synergistic influence of sodium dodecyl benzene sulfonate (SDBS) and various nanomaterials, and the lowest amount of residual oil was 37.84% after multiwalled carbon nanotubes-SDBS flooding. Dai et al prepared nanofluid with silica nanoparticles and nonionic surfactant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the use of nanoparticles (NPs) has received widespread attention for its potential EOR applications. NPs are particles typically ranging from 1 to 100 nm in size. Several types of nanomaterials have been studied for application in EOR, including titanium dioxide, ,, graphene, silica dioxide, , aluminosilicate, zirconium dioxide, ,, and silica dioxide in the CO 2 -brine system. , Laboratory investigations have demonstrated that the surfactant performance can be enhanced by combining the surfactant solution with nanomaterials to improve the interfacial properties between the oil–water-rock system. ,,,,, Nourinia et al . reported that adding zinc oxide/monmorillonite nanocomposites into a natural surfactant derived from cyclamen persicum reduced the IFT to a minimum of 2.5 mN/m.…”
Section: Introductionmentioning
confidence: 99%
“…The global energy demand is rising and projected to increase significantly in the upcoming years , and may even increase by around 60% by 2040, primarily due to population growth, urbanization, and economic development in many countries. Crude oil is the principal source of energy worldwide, and the increasing number of depleted oil reservoirs (containing approximately 70% of the remaining crude oil) requires immediate attention. , Hence, the development of innovative production enhancement strategies is essential in order to cope with the increasing energy demand and to optimize recovery from existing hydrocarbon fields. , Several enhanced oil recovery (EOR) methods, such as chemical EOR and thermal EOR, are used to increase the recovery and sweep efficiency during water flooding and gas injection. In this respect, the wettability of the rock is an essential parameter for improving the trapped oil recovery and sweep efficiency. , However, subsurface formations are naturally contaminated with organic acids, which renders them hydrophobic and leads to the early breakthrough of injected fluid, which leaves behind large volumes of hydrocarbons. , …”
Section: Introductionmentioning
confidence: 99%